2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside ameliorates bleomycin-induced pulmonary fibrosis via regulating pro-fibrotic signaling pathways - Huang, Tsung-Teng; Chen, Chuan-Mu; Chen, Lih-Geeng; Lan, Ying-Wei; Huang, Tse-Hung; Choo, Kong Bung; Chong, Kowit-Yu (Frontiers in Pharmacology, 2022)
2,3,5,4′-Tetrahydroxystilbene-2-O-β-D-Glucoside (THSG) is the main active ingredient extracted from Polygonum multiflorum Thunb. (PMT), which has been reported to possess extensive pharmacological properties. Nevertheless, the exact role of THSG in pulmonary fibrosis has not been demonstrated yet. The main purpose of this study was to investigate the protective effect of THSG against bleomycin (BLM)-induced lung fibrosis in a murine model, and explore the underlying mechanisms of THSG in transforming growth factor-beta 1 (TGF-β1)-induced fibrogenesis using MRC-5 human lung fibroblast cells. We found that THSG significantly attenuated lung injury by reducing fibrosis and extracellular matrix deposition. THSG treatment significantly downregulated the expression levels of TGF-β1, fibronectin, α-SMA, CTGF, and TGFBR2, however, upregulated the expression levels of antioxidants (SOD-1 and catalase) and LC3B in the lungs of BLM-treated mice. THSG treatment decreased the expression levels of fibronectin, α-SMA, and CTGF in TGF-β1-stimulated MRC-5 cells. Conversely, THSG increased the expression levels of SOD-1 and catalase. Furthermore, treatment of THSG profoundly reduced the TGF-β1-induced generation of reactive oxygen species (ROS). In addition, THSG restored TGF-β1-induced impaired autophagy, accompany by increasing the protein levels of LC3B-II and Beclin 1. Mechanism study indicated that THSG significantly reduced TGF-β1-induced increase of TGFBR2 expression and phosphorylation of Smad2/3, Akt, mTOR, and ERK1/2 in MRC-5 cells. These findings suggest that THSG may be considered as an anti-fibrotic drug for the treatment of pulmonary fibrosis.